The Utilization of Islamic-Based English Dialogue for Teaching and Learning English at School - Sopha, Diana; Risnawaty, Risnawaty; Yuliana, Yayuk; Silalahi, Cita Ayni Putri (Forum Kerjasama Pendidikan Tinggi, 2026)
English language proficiency plays an increasingly important role in supporting the quality of secondary education, including within Islamic-based schools that emphasize the integration of academic excellence and religious values. SMA Sains Tahfidz Qur’an Al-Ammar Deli Serdang, as a Tahfidz-oriented institution, faces specific challenges in English instruction, particularly in developing spoken dialogues that are both communicative and aligned with Islamic contexts. Many teachers experience limitations in designing and implementing English dialogue activities that reflect religious practices and everyday school life. In response to this condition, a community service program was conducted to provide Islamic-based English dialogue training for teachers. The main objective of this program was to enhance teachers’ understanding, pedagogical insight, and readiness to develop and apply communicative English dialogues that are contextually relevant to Islamic educational settings. The program involved teachers of SMA Sains Tahfidz Qur’an Al-Ammar Deli Serdang as active partners throughout all stages of the activity. The implementation method included needs analysis, training material development, workshop-based training sessions, mentoring, and evaluation. Program outcomes were assessed using a quantitative approach through pre-test and post-test instruments, as well as qualitative methods such as observation and participant reflection. The findings indicate a noticeable improvement in teachers’ conceptual understanding of Islamic-based English dialogues, increased confidence in using spoken English, and greater preparedness to implement meaningful dialogue-based instruction in the classroom. Overall, this community service activity contributed positively to strengthening the quality and relevance of English language learning in an Islamic school context.